Real Time Remote Wireless Sensor Network for Water Quality Monitoring - Gupta, Archna; Rani, Pooja; Singh, Yashwant (International Journal of Computer Sciences and Engineering, 2025)
Water contamination is one of the significant apprehensions for the green globalization. Potable water is really a scarce resource to today’s generation. Urbanization, overpopulation, industrialization, has lead to tremendous increase in untreated sewage disposal and industrial effluents. This has lead to spread of life threatening diseases. Water surveillance is an important tool to control the level of contamination in the polluted water. In India, water quality is analyzed by manual water quality surveillance methods which exacerbate water quality deterioration. Therefore, the need of a continuous, real-time, in-situ monitoring system for water quality management has risen. Wireless Sensor Network (WSN) which is real-time, continuous and dynamic system has fascinated us for pro-active water quality management. Though there are a number of research papers available on the working of WSN in different areas, the studies on application of WSN in environmental monitoring remains limited. In this paper, we discuss requirement and suitability of WSN for water quality surveillance. This research work deals with clustering approach which will be energy efficient to increase the lifespan of the network. Then the optimization approach is implemented to optimize the performance of the network.